2010
DOI: 10.1111/j.1750-3841.2010.01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Anthocyanin Extraction from Red Cabbage Using Pulsed Electric Field Processing

Abstract: :  This study was conducted to evaluate the effect of pulsed electric field (PEF) treatment on anthocyanin extraction from red cabbage using water as a solvent. Mashed cabbage was placed in a batch treatment chamber and subjected to PEF (2.5 kV/cm electric field strength; 15 μs pulse width and 50 pulses, specific energy 15.63 J/g). Extracted anthocyanin concentrations (16 to 889 μg/mL) were determined using HPLC. Heat and light stabilities of the control and PEF‐treated samples, having approximately the same i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 34 publications
0
41
0
1
Order By: Relevance
“…Anthocyanins were also extracted from red cabbage by PEF treatment [39]. These authors showed that PEF treatment enhanced total extraction of anthocyanins in water 2.15 times with a higher proportion of non-acylated forms than control.…”
Section: Applicationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Anthocyanins were also extracted from red cabbage by PEF treatment [39]. These authors showed that PEF treatment enhanced total extraction of anthocyanins in water 2.15 times with a higher proportion of non-acylated forms than control.…”
Section: Applicationsmentioning
confidence: 91%
“…PEF was demonstrated to improve mass-transfer processes, resulting in greater extraction of different hydrophilic intracellular materials {e.g., polyphenols from a large number of fruits, vegetables and agricultural waste [38][39][40][41], sucrose from the sugar beet [42], and betalains from red beets [43]}. These references provide a brief overview of the many applications of PEF-assisted extraction of valuable compounds from natural products ( Table 4).…”
Section: Applicationsmentioning
confidence: 99%
“…HP is described as a technique with ability to induce protein unfolding, leading to loss of enzyme activity [Ludikhuyze et al, 2003], while PEF processing may lead to inactivation of enzymes at certain processing conditions, maybe due to interference from the electric pulses with metal co-factors or due to local Joule heating [Aguiló-Aguayo et al, 2008. Only a few studies have dealt with PEF treatment of Brassica plants [Gachovska et al, 2010;Guderjan et al, 2007], and none of these has investigated the effects of PEF on glucosinolates and myrosinase.…”
Section: Unauthenticatedmentioning
confidence: 99%
“…HP is described as a technique with ability to induce protein unfolding, leading to loss of enzyme activity [Ludikhuyze et al, 2003], while PEF processing may lead to inactivation of enzymes at certain processing conditions, maybe due to interference from the electric pulses with metal co-factors or due to local Joule heating [Aguiló-Aguayo et al, 2008. Only a few studies have dealt with PEF treatment of Brassica plants [Gachovska et al, 2010;Guderjan et al, 2007], and none of these has investigated the effects of PEF on glucosinolates and myrosinase.Brassicaceae plants are rich in bioactive compounds including those considered as health promoting phytochemicals such as glucosinolates [Andersen et al, 2010a;Holst & Williamson, 2004; Jeffery & Aray, 2009;Sørensen et al, 2001]. Glucosinolates and their degradation products in broccoli and other cruciferous vegetables have as group attracted much attention owing to their odor and "taste" [Hansen et al, 1995[Hansen et al, , 1997.…”
mentioning
confidence: 99%
“…So far, many anthocyanin extraction methods such as conventional acidified water (Soxhlet extraction), ultrasound, high pressure extraction with CO 2 and co-solvents, microwave pre-treatment, accelerated fluid extraction and pulsed electric field (PEF) have been proposed by researchers [2], [3], [4], [5], [6], [7], [8], [9], [10]. However, several drawbacks of the methods were reported such as time consuming, insufficient rate, degradation of anthocyanin due to high temperature use, hydrolysis of anthocyanin by using acidified organic solvents; and no single extraction method could be applied for all plants.…”
Section: Introductionmentioning
confidence: 99%